PENGGUNAAN METODE BERMAIN PERAN UNTUK PENINGKATAN KEMAMPUAN BERBICARA PADA SISWA KELAS V SD INPRES TUREKISA KECAMATAN GOLEWA BARAT KABUPATEN NGADA - Marselina Wali (Jurnal Akrab Juara, 2019)
Indonesian language learning in 2013 curriculum generally aims to improve students' ability to communicate in Indonesian properly and correctly, both oral and written. The research questions are; how is the implementation of the role playing method in SD Inpres Turekisa and how are students' speaking abilities after using the role playing method?. This study uses study Classroom Action Research and the data were analyzed qualitatively. The use of role playing methods can improve the speaking skills of fifth grade students in the SD Inpres Turekisa because students play a daily role in their life. Role playing can relieve the teacher in teaching because it is more likely to achieve learning goals when compared to the use of lecture and question and answer methods. By acting alone, students will better understand and understand problems and they are also trained to portray the characters in the story. In addition, role playing can train students' speaking skills properly and correctly. The results shows that role playing method can improve students' speaking abilities with an average in each cycle, namely: cycle I: 2.82, cycle II: 3.64, and cycle III: 4.54. thus, it can be concluded that role playing through various children's stories can improve the speaking skills of fifth grade students very good.